Persepsi Siswa Atas Kompetensi Sosial Guru dan Minat Belajar terhadap Prestasi Belajar Matematika - Asmar Asmar (JKPM (Jurnal Kajian Pendidikan Matematika), 2018)
The purpose of this study was to determine the impacts of student’s perception on teacher’s social competence and learning interest on mathematics learning achievement. The research was conducted on students of class VII in Imanuel Junior High School and Pa Van Des Teur Junior High School, Pondok Melati, East Jakarta. This study is corelasional survey research with regression analysis. Based on research results, it can be concluded that both of student’s  perception on teacher’s social competence and learning interest give positive influence and significantly on mathematics learning achievement and also together student’s perception on teacher’s social competence and learning interests give positive impacts and significantly on mathematics learning achievement.